Practical C - Zambon, Giulio (Apress : Imprint: Apress, 2016)
Learn practical C techniques, including often-needed algorithms within reusable functions. In this book, you'll have the following code and advice at your fingertips: layout and pre-processors; control structures, iterations, and selections; pointers and structures; databases; reusability; lists, arrays, FIFO and stacks; searching and sorting; recursion; binary trees; integration; string utilities in/outside of C; web serving using Mongoose; game application code to build a MathSearch puzzle; and embedded software. Besides providing you with modules that you can immediately put to use, Practical C also teaches you how to leverage the C language in a way that beginner books cannot achieve. What You Will Learn: Avoid pitfalls that can cause intractable problems Handle lists and arrays Perform searches and sorts Binary trees Take advantage of recursion Handle exceptions Access databases Calculate integrals using numerical computation with practical applications Deal with strings in a convenient, error-free way Build a MathSearch game application, similar to WordSearch puzzle games Deal with issues specific to embedded applications Who This Book Is For Programmers who have a general knowledge of C. .